2008
DOI: 10.1128/jcm.00478-08
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Four Selective Agars and Two Enrichment Broths in Screening for Methicillin-Resistant Staphylococcus aureus

Abstract: To evaluate methicillin-resistant Staphylococcus aureus detection, we tested in vitro four selective agars and two enrichment broths apart and in combination. Tryptone soya broth with salt, aztreonam, and cefoxitin appeared to be the most sensitive medium. This broth was superior to a phenol red mannitol broth with aztreonam and ceftizoxime.Methicillin-resistant Staphylococcus aureus (MRSA) is a major cause of morbidity and mortality worldwide. Detection of MRSA in screening samples is an important part of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 16 publications
(16 reference statements)
0
22
0
Order By: Relevance
“…We did not study the specific effects of enrichment, as no direct inoculation was performed. In a previous study, Böcher et al (2) showed no increase in yield after selective enrichment, whereas other studies showed that an enrichment step in combination with chromogenic agars led to increased sensitivities of 14 to 26% (11) and 12% (16), respectively.…”
mentioning
confidence: 99%
“…We did not study the specific effects of enrichment, as no direct inoculation was performed. In a previous study, Böcher et al (2) showed no increase in yield after selective enrichment, whereas other studies showed that an enrichment step in combination with chromogenic agars led to increased sensitivities of 14 to 26% (11) and 12% (16), respectively.…”
mentioning
confidence: 99%
“…Because of their resistance to antimicrobials in the agar, MRSA colonies grow and subsequently produce distinct color changes caused by the cleavage of a chromogenic substrate by a specific enzyme of S. aureus. Results can be achieved in as little as 18 to 24 h of incubation, depending on the agar used (1,4,5,15,27 (2,9,16,21); however, enrichment delays results and adds to workload and costs. Thus, a discussion of the advantages and limitations of each methodological approach become critical.…”
mentioning
confidence: 99%
“…In contrast to these results, a recent study from De Silva et al (8) did not find any difference in the determination of S. aureus nasal carriage when comparing flocked swabs to rayon swabs; however, those authors used a different microbiological procedure than ours, consisting of an overnight preenrichment broth step, followed by plating on chromogenic agar. The latter process is known to improve the sensitivity of bacterial detection (3,10,13,15), but it is timeconsuming since the results are delayed by 1 day, which may be a determinant for the detection of nasal carriers when decontamination treatment must be applied to prevent S. aureus infection, for instance, just before a surgical procedure (4) or the arrival of the patient in an intensive care unit. In addition, De Silva et al provided no data relative to the amount of bacteria recovered by each type of swab (8).…”
mentioning
confidence: 99%